Preparation method of nano calcium carbonate for degradable plastics
By preparing nano calcium carbonate and utilizing the interface effect and degradation mechanism of graft copolymers, the problem of insufficient strength and degradation performance of degradable plastics is solved, and the strength improvement of the material and the acceleration of degradation efficiency are achieved.
Patent Information
- Application Number
- CN202510336534.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing biodegradable plastics have problems with insufficient strength and load-bearing capacity in terms of physical properties, which limits their widespread use in practical applications.
By preparing nano calcium carbonate, the dual interface effect of graft copolymer A/B is used to reduce the interface defects between nano calcium carbonate particles and the plastic matrix, and the microbial attachment sites and degradation mechanism are introduced through graft copolymers of amylose and polylactic acid, thereby improving the strength and degradation efficiency of the material.
It has achieved the improvement of the tensile strength and degradation properties of the biodegradable plastic, and enhanced its use value in practical applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano calcium carbonate, in particular to a method for preparing nano calcium carbonate for degradable plastics. Background Art
[0002] Degradable plastics refer to polymer materials that, under specific environmental conditions (microorganisms, humid and hot environment, light, etc.), are eventually converted into carbon dioxide, water and biomass through chemical bond breaking and biological assimilation.
[0003] However, despite the significant environmental advantages of biodegradable plastics, in practical applications, their physical properties, especially strength and load-bearing capacity, often become key factors limiting their widespread application. In contrast, although paper bags or paper-plastic composite products are better than pure plastic products in terms of degradation performance, their strength is usually lower and it is difficult to meet some occasions with high requirements for load-bearing capacity. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing nano calcium carbonate for degradable plastics, aiming to improve the strength and degradability of plastic products. The method is specifically achieved through the following technical solutions: A method for preparing nano calcium carbonate for degradable plastics comprises the following preparation steps: S1, quicklime and water were mixed in a mass ratio of 1:5, stirred and digested at 80℃ for 45min, and a three-stage cyclone separator was used to remove particulate impurities to obtain Ca(OH) 2 Serum; S2, by Ca(OH) 2 The dry basis weight of the slurry is calculated, 0.5% to 1.5% of the chelating agent is added, mixed and stirred for 10 to 15 minutes, and the formed chelate is filtered out by a filter press to obtain refined Ca(OH) 2 Serum; S3, refine Ca(OH) 2 The slurry was transferred to the carbonization reactor and refined Ca(OH) 2 The crystal form regulator with a dry weight of 0.8% to 1.5% of the slurry is introduced into the C0 2 / N 2 The mixed gas is subjected to carbonization reaction, the reaction temperature is controlled at 25±3°C, the stirring rate is 400rpm, the pH value is reduced to 7.5, and the introduction is stopped to obtain a nano calcium carbonate slurry with a cubic crystal shape; S4, polyether diol, maleic anhydride, initiator according to the mass ratio of (45 ~ 55): (15 ~ 20): (1 ~ 1.5) were added to the reaction kettle A, and reacted at 180 ° C for 3 ~ 4h under nitrogen protection to obtain a graft copolymer A; S5, polylactic acid, amylose, dibutyltin dilaurate, and glycerol were added to the reaction kettle B in a mass ratio of (25-35): (8-15): (0.2-0.5): (0.5-1), and grafted at 145°C for 1.5-2h under nitrogen protection to obtain a graft copolymer B; S6, heating the carbonized nano-calcium carbonate slurry to 70-75° C., adding 3%-5% of the graft copolymer A and 1%-3% of the graft copolymer B to the nano-calcium carbonate slurry on a dry basis, and dispersing by ultrasonication to obtain a modified nano-calcium carbonate slurry; S7. The modified nano-calcium carbonate slurry is filtered and spray-dried to finally obtain powdered nano-calcium carbonate.
[0005] Preferably, when adding the crystal form regulator, the crystal form regulator to be added is dissolved in deionized water to prepare a regulating solution with a mass concentration of 10%, and the solution is slowly added dropwise by a peristaltic pump.
[0006] Preferably, in step S3, the refined Ca(OH) 2 When the pH of the slurry drops to 10.5, 60% to 70% of the total volume of the regulating liquid is added, and the remaining 30% to 40% of the regulating liquid is added when the pH drops to 9.5.
[0007] Preferably, the drip acceleration rate of the peristaltic pump is 0.5-1.0 L / min.
[0008] Preferably, the crystal form regulator is prepared by mixing trisodium phosphate and sodium citrate in a mass ratio of (3-5):3.
[0009] Preferably, the chelating agent is modified sodium gluconate.
[0010] Preferably, the C0 2 / N 2 C0 in mixed gas 2 The volume fraction is 30% to 70%.
[0011] Preferably, the initiator is dicumyl peroxide.
[0012] After adopting the above technical solution, the beneficial effects of the present invention are: The dual interface effect of graft copolymer A / B reduces the interface defects between nano calcium carbonate particles and plastic matrix and improves tensile strength. Amylose grafting introduces α-1,4 glycosidic bonds to provide microbial attachment sites. Polylactic acid is hydrolyzed to generate lactic acid in a hot and humid environment, which reduces the local pH, dissolves nano calcium carbonate, and accelerates degradation efficiency. DETAILED DESCRIPTION
[0013] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.
[0014] Example 1 The present invention provides a method for preparing nano calcium carbonate for degradable plastics, comprising the following preparation steps: S1. Limestone calcination and digestion The limestone is crushed into particles of 20 to 30 mm to ensure uniform heat transfer during calcination. The limestone particles are placed in a rotary kiln and calcined at a high temperature of 1050°C for 2.5 hours to obtain quicklime. Quicklime and water are mixed in a mass ratio of 1:5, and the mixed materials are stirred and digested at 80°C for 45 minutes. After the digestion reaction is completed, it is placed in an aging tank for aging for no less than 24 hours. The aged slurry is removed from particulate impurities using a three-stage cyclone separator to obtain Ca(OH) 2 Serum.
[0015] S2. Chelating agent treatment According to the given Ca(OH) 2 slurry, add 0.5% of the dry weight of modified sodium gluconate as a chelating agent, mix and stir for 10 minutes. Filter the formed chelate through a filter press to obtain refined Ca(OH) 2 Serum.
[0016] The modification steps of modified sodium gluconate are as follows: 1) Dissolve 100g sodium gluconate in 300mL deionized water and stir until completely dissolved. In another container, dissolve 30g polyethyleneimine in 200mL ethanol to form a uniform solution. 2) At room temperature, slowly add the polyethyleneimine solution to the sodium gluconate solution with a stirring rate of 500 rpm. After the addition is completed, add 25 g of epichlorohydrin and adjust the pH to 10 with a NaOH solution. Raise the temperature to 45°C and react for 6 hours with a stirring rate of 400 rpm. 3) The pH was adjusted to neutral with dilute hydrochloric acid to terminate the reaction, unreacted epichlorohydrin and by-products were removed by centrifugation, the precipitate was washed three times with ethanol / water solution (volume ratio 1:1) to remove residual impurities, vacuum dried and ground to obtain a powdery solid.
[0017] The epoxy group of epichlorohydrin is ring-opened and reacts with the hydroxyl group of sodium gluconate and the amino group of polyethyleneimine, respectively, to form a stable ether bond and amine bond cross-linked network. The unreacted carboxylic acid group and hydroxyl group are distributed on the surface of the network to provide chelating sites. The micropores formed after cross-linking shield the approach of calcium ions through steric hindrance. At the same time, the unreacted amino groups in the cross-linked network are positively charged, further repelling calcium ions. The exposed carboxylic acid group and hydroxyl group preferentially bind to iron ions and magnesium ions through coordination bonds to form stable chelates.
[0018] S3. Carbonization and crystal form control Trisodium phosphate and sodium citrate are selected as crystal form regulators to regulate the crystal form of nano calcium carbonate slurry. Trisodium phosphate and sodium citrate are compounded in a mass ratio of 1:1, and then dissolved in deionized water to prepare a 10% mass concentration regulating solution. The total mass of the crystal form regulator accounts for 10% of the refined Ca(OH) 2 0.8% of the dry mass of the slurry. 2 The slurry was transferred to the carbonization reactor and CO was introduced from the bottom at a flow rate of 0.5 L / min. 2 / N 2 Mixed gas (C0 2 The volume fraction of the carbonization reaction was 30%). The reaction temperature was controlled at 22°C and the stirring rate was 400 rpm.
[0019] Lower concentrations of C0 2 It is conducive to the formation of nano-calcium carbonate. If the concentration is too high, the reaction speed will be too fast and gelation will easily occur. After the carbonization starts, when the pH monitoring point detects that the pH of the system has dropped to 10.5, the peristaltic pump pumps in 60% of the total volume of the regulating liquid at a dripping rate of 0.5L / min. Inhibit the rapid growth of calcite-type crystal nuclei and preferentially form cubic primary crystal nuclei. When the system drops to 9.5, add the remaining 40% of the regulating liquid. Further stabilize the growth of the crystal surface and avoid the formation of chain or needle-like structures. When the pH of the system drops to 7.5, stop the C0 2 , and obtain a nano calcium carbonate slurry with a cubic crystal shape.
[0020] S4. Preparation of graft copolymer A Polyether diol, maleic anhydride and dicumyl peroxide were added to reactor A in a mass ratio of 45:15:1, and reacted at 180°C for 3 hours under nitrogen protection to obtain graft copolymer A. Dicumyl peroxide, as an initiator, decomposed under heat to generate free radicals, which initiated the graft copolymerization of maleic anhydride and polyether diol.
[0021] S5. Preparation of graft copolymer B Polylactic acid, amylose, dibutyltin dilaurate and glycerol were added into reactor B in a mass ratio of 25:8:0.2:0.5, and grafted at 145°C for 1.5h under nitrogen protection to obtain graft copolymer B.
[0022] Glycerol can destroy the hydrogen bonds between starch molecules, expose the hydroxyl active sites, and inhibit the carbonization of amylose at high temperatures. Dibutyltin dilaurate acts as a catalyst to break the ester bonds in polylactic acid to form lactic acid oligomers. The acyloxy groups of lactic acid oligomers attack the starch hydroxyl groups to form graft copolymers. Polylactic acid enhances the compatibility with the degradable plastic matrix, thereby improving the overall toughness of the matrix. The natural polysaccharide segments of amylose can enhance biodegradability and accelerate the enzymatic and hydrolytic processes of the material in the natural environment.
[0023] S6, Nano calcium carbonate modification The carbonized nano-calcium carbonate slurry was heated to 70°C, and 3% of the graft copolymer A was added to the nano-calcium carbonate slurry on a dry basis, and ultrasonically dispersed for 15 minutes. Then, 1% of the graft copolymer B was added to the nano-calcium carbonate slurry on a dry basis, and ultrasonically dispersed for 45 minutes to obtain a modified nano-calcium carbonate slurry.
[0024] Graft copolymer A forms a coating layer through chemical anchoring of carboxylic acid groups to the surface of nano calcium carbonate particles, which reduces the surface energy of particles, improves their dispersibility in the biodegradable plastic matrix, and reduces agglomeration. The polyether segments on graft copolymer A form hydrogen bonds with polar groups (such as ester groups) of the biodegradable plastic matrix (such as PLA), thereby improving the interfacial bonding strength.
[0025] The graft copolymer B is covered on the surface of the coating layer through physical entanglement and hydrogen bonding, and the amylose is grafted to introduce α-1,4 glycosidic bonds, providing microbial attachment sites and being compatible with the biodegradable plastic matrix. When preparing biodegradable plastics, the PLA segments of the graft copolymer B partially soften, entangle with the interchain of the biodegradable plastic matrix particles, fill the gaps between the particles, and form a continuous interface.
[0026] The dual interface effect of the graft copolymer A / B reduces the interface defects between the nano-calcium carbonate particles and the degradable plastic matrix and improves the strength.
[0027] During degradation, starch segments are degraded first, exposing the inner nano-calcium carbonate particles, forming a porous structure and increasing the specific surface area. Polylactic acid is hydrolyzed in a hot and humid environment to generate lactic acid, which reduces the local pH, dissolves the nano-calcium carbonate, and accelerates the degradation efficiency.
[0028] S7, finished product The modified nano calcium carbonate slurry is filtered and spray dried to finally obtain powdered nano calcium carbonate.
[0029] Example 2 A method for preparing nano calcium carbonate for degradable plastics comprises the following steps: S1, quicklime after limestone calcination was mixed with water in a mass ratio of 1:5, stirred and digested at 80℃ for 45min, and a three-stage cyclone separator was used to remove particulate impurities to obtain Ca(OH) 2 Serum; S2, by Ca(OH) 2 The dry basis weight of the slurry was calculated, and 1.2% of modified sodium gluconate was added, mixed and stirred for 13 minutes, and the formed chelate was filtered out by a filter press to obtain refined Ca(OH) 2 Serum; S3, refine Ca(OH) 2 The slurry was transferred to the carbonization reactor and CO was introduced from the bottom at a flow rate of 0.8 L / min. 2 / N 2 Mixed gas (C0 2 The volume fraction is 55%) for carbonization reaction, the reaction temperature is controlled at 25°C, the stirring rate is 400rpm, trisodium phosphate and sodium citrate are compounded according to a mass ratio of 4:3, and then dissolved in deionized water to prepare a 10% mass concentration control liquid. The total mass of the crystal form control agent used accounts for 10% of the refined Ca(OH) 2 When the pH monitoring point detected that the pH of the system dropped to 10.5, the peristaltic pump pumped 65% of the total volume of the regulating liquid at a dripping speed of 0.8L / min. When the pH of the system dropped to 9.5, the remaining 35% of the regulating liquid was added dropwise. When the pH of the system dropped to 7.5, the C0 2 , obtaining a nano calcium carbonate slurry having a cubic crystal shape; S4, polyether diol, maleic anhydride, dicumyl peroxide according to the mass ratio of 50:18:1.2 was added to the reactor A, and the reaction was carried out at 180 ° C for 3.5h under nitrogen protection to obtain a graft copolymer A; S5, polylactic acid, amylose, dibutyltin dilaurate, glycerol according to the mass ratio of 30:10:0.3:0.8 were added to the reactor B, and grafted at 145 ° C for 2h under nitrogen protection to obtain a graft copolymer B; S6, heating the carbonized nano-calcium carbonate slurry to 73° C., first adding 3.5% of the graft copolymer A by weight of the dry basis of the nano-calcium carbonate slurry, ultrasonically dispersing for 20 min, and then adding 1.5% of the graft copolymer B by weight of the dry basis of the nano-calcium carbonate slurry, ultrasonically dispersing for 50 min, to obtain a modified nano-calcium carbonate slurry; S7. The modified nano-calcium carbonate slurry is filtered and spray-dried to finally obtain powdered nano-calcium carbonate.
[0030] Example 3 A method for preparing nano calcium carbonate for degradable plastics comprises the following steps: S1, quicklime after limestone calcination was mixed with water in a mass ratio of 1:5, stirred and digested at 80℃ for 45min, and a three-stage cyclone separator was used to remove particulate impurities to obtain Ca(OH) 2 Serum; S2, by Ca(OH) 2 The dry basis weight of the slurry was calculated, and 1.5% modified sodium gluconate was added, mixed and stirred for 15 minutes, and the formed chelate was filtered out by a filter press to obtain refined Ca(OH) 2 Serum; S3, refine Ca(OH) 2 The slurry was transferred to the carbonization reactor and CO was introduced from the bottom at a flow rate of 1.2 L / min. 2 / N 2 Mixed gas (C0 2 The volume fraction is 70%) for carbonization reaction, the reaction temperature is controlled at 28°C, the stirring rate is 400rpm, trisodium phosphate and sodium citrate are compounded according to a mass ratio of 5:3, and then dissolved in deionized water to prepare a 10% mass concentration control liquid. The total mass of the crystal form control agent used accounts for 10% of the refined Ca(OH) 2 After carbonization begins, when the pH monitoring point detects that the pH of the system drops to 10.5, the peristaltic pump pumps 70% of the total volume of the regulating liquid at a dripping speed of 1L / min. When the pH of the system drops to 9.5, the remaining 30% of the regulating liquid is added dropwise. When the pH of the system drops to 7.5, the C0 is stopped. 2 , obtaining a nano calcium carbonate slurry having a cubic crystal shape; S4, polyether diol, maleic anhydride, dicumyl peroxide according to the mass ratio of 55:20:1.5 was added to the reactor A, and the reaction was carried out at 180 ° C for 4h under nitrogen protection to obtain a graft copolymer A; S5, polylactic acid, amylose, dibutyltin dilaurate, glycerol according to the mass ratio of 35:15:0.5:1 was added to the reactor B, and grafted at 145 ° C for 2.5h under nitrogen protection to obtain a graft copolymer B; S6, heating the carbonized nano-calcium carbonate slurry to 75° C., first adding 5% of the graft copolymer A by weight of the dry basis of the nano-calcium carbonate slurry, ultrasonically dispersing for 25 min, and then adding 3% of the graft copolymer B by weight of the dry basis of the nano-calcium carbonate slurry, ultrasonically dispersing for 55 min, to obtain a modified nano-calcium carbonate slurry; S7, the modified nano calcium carbonate slurry is filtered by pressure and spray dried to finally obtain powdered nano calcium carbonate.
[0031] The preparation method of a degradable plastic film based on nano calcium carbonate for degradable plastics comprises the following steps: 1) Polylactic acid and polybutylene terephthalate adipate were premixed in a mass ratio of 7:3, and 0.3% of the total mass of the chain extender ADR-4370S was added, and the mixture was melt-blended in a twin-screw extruder to form a uniform blend; 2) According to the mass percentage, 68wt% PLA / PBAT blend, 20wt% nano-calcium carbonate, 6wt% polyethylene glycol 6000, 4wt% epoxy soybean oil, 0.8wt% benzophenone, and 1.2wt% Bacillus composite bacterial agent were melt-blended and extruded into granules through a twin-screw extruder to obtain a blown film masterbatch; 3) The film blowing masterbatch is blown into film by a film blowing machine to obtain a degradable plastic film.
[0032] The nano-calcium carbonate obtained in Examples 1-3 were respectively made into plastic films, and a plastic film without nano-calcium carbonate was prepared as a control group.
[0033] According to GB / T 35795-2017, the above four plastic films were made into specimens for analyzing the mechanical properties of the plastic films. The results are shown in Table 1.
[0034] Table 1. Plastic film properties
[0035] In Example 1-3, nano calcium carbonate is added as a performance filler to form a rigid network with the matrix. Under the action of external force, stress is transmitted through the particles to reduce local stress concentration. The dual interface effect of the graft copolymer A / B reduces the interface defects between the nano calcium carbonate particles and the plastic matrix and improves the tensile strength.
[0036] According to GB / T 35795-2017, the above four types of plastic films were made into specimens for analyzing the degradation properties of the plastic films. The results are shown in Table 2.
[0037] Table 2. Degradation properties of plastic films
[0038] The amylose grafting of Examples 1-3 introduces α-1,4 glycosidic bonds to provide microbial attachment sites. The starch segments are preferentially degraded, exposing the inner layer of nano calcium carbonate particles, forming a porous structure and increasing the specific surface area. Polylactic acid is hydrolyzed in a hot and humid environment to generate lactic acid, which reduces the local pH, dissolves the nano calcium carbonate, and accelerates the degradation efficiency.
[0039] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to specific embodiments. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing nano calcium carbonate for degradable plastics, characterized in that: The method comprises the following preparation steps: S1, quicklime and water were mixed in a mass ratio of 1:5, stirred and digested at 80°C for 45 minutes, and particulate impurities were removed by a three-stage cyclone separator to obtain Ca(OH)2 slurry; S2. Add 0.5% to 1.5% of the chelating agent according to the dry basis weight of the Ca(OH)2 slurry, mix and stir for 10 to 15 minutes, and filter out the formed chelate through a filter press to obtain a refined Ca(OH)2 slurry; S3, the refined Ca (OH) 2 slurry is transferred to the carbonization reactor, and a crystal form regulator accounting for 0.8% to 1.5% of the dry basis weight of the refined Ca (OH) 2 slurry is added, and a C02 / N2 mixed gas is introduced from the bottom at a flow rate of 0.5 to 1.2 L / min for carbonization reaction, and the reaction temperature is controlled at 25 ± 3 ° C, the stirring rate is 400 rpm, the pH is reduced to 7.5, and the introduction is stopped to obtain a nano calcium carbonate slurry with a cubic crystal form; S4, polyether diol, maleic anhydride, initiator according to the mass ratio of (45 ~ 55): (15 ~ 20): (1 ~ 1.5) were added to the reaction kettle A, and reacted at 180 ° C for 3 ~ 4h under nitrogen protection to obtain a graft copolymer A; S5, polylactic acid, amylose, dibutyltin dilaurate, and glycerol were added to the reaction kettle B in a mass ratio of (25-35): (8-15): (0.2-0.5): (0.5-1), and grafted at 145°C for 1.5-2h under nitrogen protection to obtain a graft copolymer B; S6, heating the carbonized nano-calcium carbonate slurry to 70-75° C., adding 3%-5% of the graft copolymer A and 1%-3% of the graft copolymer B to the nano-calcium carbonate slurry on a dry basis, and dispersing by ultrasonication to obtain a modified nano-calcium carbonate slurry; S7. The modified nano-calcium carbonate slurry is filtered and spray-dried to finally obtain powdered nano-calcium carbonate.
2. The method for preparing nano calcium carbonate for degradable plastics according to claim 1, wherein: When adding the crystal form regulator, the crystal form regulator to be added is dissolved in deionized water to prepare a regulating solution with a mass concentration of 10%, and the solution is slowly added dropwise by a peristaltic pump.
3. The method for preparing nano calcium carbonate for degradable plastics according to claim 2, wherein: In step S3, when the pH of the refined Ca(OH)2 slurry drops to 10.5, 60% to 70% of the total volume of the regulating solution is added, and the remaining 30% to 40% of the regulating solution is added when the pH drops to 9.
5.
4. The method for preparing nano calcium carbonate for degradable plastics according to claim 3, characterized in that: The drip acceleration rate of the peristaltic pump is 0.5-1.0 L / min.
5. The method for preparing nano calcium carbonate for degradable plastics according to claim 4, characterized in that: The crystal form regulator is prepared by mixing trisodium phosphate and sodium citrate in a mass ratio of (3-5):
3.
6. The method for preparing nano calcium carbonate for degradable plastics according to claim 1, characterized in that: The chelating agent is modified sodium gluconate.
7. The method for preparing nano calcium carbonate for degradable plastics according to claim 1, characterized in that: The volume fraction of C02 in the C02 / N2 mixed gas is 30% to 70%.
8. The method for preparing nano calcium carbonate for degradable plastics according to claim 1, characterized in that: The initiator is dicumyl peroxide.
Citation Information
Patent Citations
Method for preparing special nano calcium carbonate for plastic master batch
CN103897434A
Preparation technology of special nano calcium carbonate for plastic degradation
CN113716593A
Preparation method of nano-scale calcium carbonate for transparent plastic master batch
CN117800377A
Concrete repairing and reinforcing mortar composition comprising surface modified nano calciumcarbonate ultra fine powder and concrete repairing and reinforcing method thereof
KR102603918B1
Cited By
Magnesium alloy calcium carbonate conversion film and preparation method thereof
CN122147303A
System and method for carbon dioxide capture for calcium carbonate production
CN122516793A